Duality of Large Fock Spaces in Several Complex Variables and Compact Localization Operators - Youqi Liu; Xiaofeng Wang (Journal of Function Spaces)
In this paper, dual spaces of large Fock spaces Fϕp with 0<p<∞ are characterized. Also, algebraic properties and equivalent conditions for compactness of weakly localized operators are obtained on Fϕp0<p<∞.